1995
DOI: 10.1113/jphysiol.1995.sp020574
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testosterone on synaptic efficacy at neuromuscular junctions in a sexually dimorphic muscle of male frogs.

Abstract: 1. The effects of testosterone on synaptic efficacy were studied in the flexor carpi radialis, a sexually dimorphic forelimb muscle involved in frog clasping behaviour. Male Xenopus laevis frogs were castrated and then given either testosterone-filled implants (CT frogs) or empty implants (C frogs) for 2, 8 or 16 weeks. 2. Intracellular recordings were made from fibres in the shoulder region and in a region midway between the elbow and wrist. These regions are mainly innervated by spinal nerve 2 (SN2) and spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
3

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
0
7
0
3
Order By: Relevance
“…Furthermore, testosterone increases intracellular calcium in myocytes producing increases in phosphorylation and transcription factors through a G proteinlinked receptor (16). In agreement, testosterone administration to myocytes decreases the action potential threshold and increases synaptic facilitation resulting in an enhancement of synaptic efficiency in the flexor carpi radialis muscle of the frog (43). Thus, testosterone can have relatively fast effects on the function of the myocyte that would affect the efficacy of synaptic transmission through phosphorylation of ion channels.…”
Section: Interactions Between Asic3 and Testosteronementioning
confidence: 54%
See 1 more Smart Citation
“…Furthermore, testosterone increases intracellular calcium in myocytes producing increases in phosphorylation and transcription factors through a G proteinlinked receptor (16). In agreement, testosterone administration to myocytes decreases the action potential threshold and increases synaptic facilitation resulting in an enhancement of synaptic efficiency in the flexor carpi radialis muscle of the frog (43). Thus, testosterone can have relatively fast effects on the function of the myocyte that would affect the efficacy of synaptic transmission through phosphorylation of ion channels.…”
Section: Interactions Between Asic3 and Testosteronementioning
confidence: 54%
“…In contrast, several studies show an increase in muscle strength following testosterone replacement therapy in men with low levels of testosterone (5,6,18), and testosterone enhances force and resistance to fatigue in normal males (2,65). In parallel, androgen receptors are located on muscle fibers (1,42) and long-term treatment of orchidectomized male mice with testosterone alters the neuromuscular junction to enhance synaptic efficacy (43). The effect of fatigue after testosterone treatment is muscle type-specific being observed in the soleus muscle Type I fibers but not in the extensor digitorum longus muscle Type II fibers (2).…”
mentioning
confidence: 97%
“…In mouse diaphragm, facilitation was examined over a range of quantal contents similar to that used in this study (0.1-3.0); again, no correlation between strength and facilitation was found (Bain and Quastel 1992). A variation in facilitation without a variation in strength has been demonstrated in another androgensensitive muscle of X. laevis: in the flexor carpi radialis, testosterone enhances facilitation without affecting release to a single stimulus (Nagaya and Herrera 1995). Mallart and Martin's (1968) study of frog sartorius showed that there was some dependence of facilitation on quantal content but only for the weakest synapses.…”
Section: Discussionmentioning
confidence: 66%
“…Subsequently, a greater force was produced and testosterone concentration was elevated. Additionally, an acute increase in testosterone can directly influence force production by facilitating neurotransmitter release (Nagaya and Herrera 1995). Thus, the ingestion of caffeine, together with acute elevations in plasma testosterone may act synergistically on the CNS to directly increase force production and improve performance.…”
Section: Discussionmentioning
confidence: 98%